Analysis of CNT additives in porous layered thin film lubrication with electric double layer - Rao, T.V.V.L.N. (American Institute of Physics Inc., 2015)
This paper presents an analysis of thin film lubrication of porous layered carbon nanotubes (CNTs) additive slider bearing with electric double layer. The CNTs additive lubricant flow in the thin fluid film and porous layers are governed by Stokes and Brinkman equations respectively, including electro-kinetic force. The apparent viscosity and nondimensional pressure expression are derived. The nondimensional load capacity increases under the influence of electro-viscosity, CNT additives volume fraction, permeability and thickness of porous layer. A CNTs additive lubricated porous thin film slider bearing with electric double layer provides higher load capacity. Â© 2015 AIP Publishing LLC.